2009
DOI: 10.1088/1748-6041/4/5/055007
|View full text |Cite
|
Sign up to set email alerts
|

Gel-derived bioglass as a compound of hydroxyapatite composites

Abstract: Despite the excellent biocompatibility of hydroxyapatite and bioglass, their clinical applications are limited to non-load-bearing implants and implant coatings due to their low mechanical properties. We have developed two different composites made of hydroxyapatite (HA) and gel-derived bioglasses designated S2 (80 mol% SiO(2)-16 mol% CaO-4 mol% P(2)O(5)) or A2 (40 mol% SiO(2)-54 mol% CaO-6 mol% P(2)O(5)). We show that the combination of hydroxyapatite with either bioglass results in better composite bioactivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 17 publications
2
32
0
Order By: Relevance
“…These data, together with cell viability results may also suggest that S2 SBG addition to TiO 2 matrix is beneficial to cell growth regardless of S2 SBG content, but if these composites are to stimulate cell differentiation the S2:TiO 2 ratio should be low (i.e., 25 wt % SBG). Previously, we showed that incorporation of gel‐derived bioactive glass into hydroxyaptite or PLGA matrix enhances osteogenic potential of human BMSCs . This work confirms our previous findings and extends the application of these gel‐derived bioglasses to TiO 2 containing biomedical devices and implants.…”
Section: Resultssupporting
confidence: 89%
“…These data, together with cell viability results may also suggest that S2 SBG addition to TiO 2 matrix is beneficial to cell growth regardless of S2 SBG content, but if these composites are to stimulate cell differentiation the S2:TiO 2 ratio should be low (i.e., 25 wt % SBG). Previously, we showed that incorporation of gel‐derived bioactive glass into hydroxyaptite or PLGA matrix enhances osteogenic potential of human BMSCs . This work confirms our previous findings and extends the application of these gel‐derived bioglasses to TiO 2 containing biomedical devices and implants.…”
Section: Resultssupporting
confidence: 89%
“…Encouragingly, HA/BG surpasses OsteoZip in most aspects of osteoconductivity. This is not surprising as it has been previously shown that gel-derived HA/BG composites demonstrated better bioactivity and biocompatibility compared to HA alone (Cholewa-Kowalska et al, 2009).…”
Section: Cell Differentiation and Cell Detachmentmentioning
confidence: 56%
“…We showed that CaO:SiO 2 ratio in these glasses influenced their physical and chemical properties and affected the growth and differentiation of bone marrow-derived cells 6,17,20. Our data further indicate that incorporation of these gel-derived glasses into a HA matrix enhanced growth and osteogenic differentiation of human mesenchymal stem cells (MSC) 5. Recently, Wu et al 41 suggested that PLGA-based composites prepared with a sol–gel derived mesoporous bioactive glass possess advantageous mechanical and biological properties compared to those containing non-mesoporous bioactive glass.…”
Section: Introductionmentioning
confidence: 60%